Study on the Use of Micro-Perforated Panel to Improve Acoustic Performance in Mosque - Putra, Azma; Kassim, Dayang H.; Yakoob, Mohd. d; Nor, M. J. M (Trans Tech Publications, 2013)
Most activities in mosque such as Friday prayer and the sermon by an Imam require clarity of speech. Unfortunately, this ‘speech intelligibility’ performance is often poor due toinitial design of a mosque. This paper presents assessment of the indoor acoustics of a mosque. Acoustical properties such as reverberation time, clarity and early decay time are obtained from simulation data using CATT indoor acoustic software. The studystarted with anempty mosque with no acoustic treatment. Acoustic ‘green’ absorbers using micro-perforated panel (MPP) are then introduced to improve the acoustic performance. The application of MPP is still rare for mosque and is expected to replace the typical porous absorber. The effect of the panel size, location and frequency range of sound absorption are simulated and the results are discussed.